Determinants of Female Juvenile Delinquency: Evidence From Indonesia - Dede Ahmad Supriatna; Hufad, Achmad; Saepudin, Asep; Sutarni, Nani; Rosmia, Ade Romi (Journal of Ecohumanism, 2024)
Adolescence is a transition period for girls to adulthood. They are generally aged 12 to 19 years. Young women are the nation’s successors expected to build a bright future. However, currently, the phenomenon of female juvenile delinquency is ubiquitous in society. This research aims to analyze the factors that influence female juvenile delinquency. The method used in this research is a quantitative method by distributing offline and online surveys to teenage girls who have undergone juvenile delinquency rehabilitation. Data was obtained from 162 responses and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) model. The conclusion of this research is that female juvenile delinquency is influenced by the variables of physical abuse, sexual activity, dropping out of school, gang involvement, poverty, drug and alcohol use or abuse, co-defendant involvement in crimes, and parental influence factors. The most dominant variables that influence female juvenile delinquency are poverty and drug and alcohol use or abuse.